Bridging the Gap: Language Learning as a Tool for Cultural Empathy at Prima Bangsa Institute: Penelitian - Putra Darma, Virga; Alting, Wasim; Aliya Zahwa, Ajeng (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This qualitative narrative inquiry delves into the intricate relationship between foreign language learning and the cultivation of cultural empathy among students enrolled in the English and Japanese language programs at Prima Bangsa Institute. Employing a narrative inquiry approach, the study meticulously analyzes the lived experiences, perceptions, and transformative journeys of five purposively selected students through in-depth, semi-structured interviews. The emergent findings unequivocally demonstrate that a culturally contextualized and experiential learning environment rich with authentic materials such as contemporary music, popular anime, structured debates, and interactive speaking events significantly enhances learners' cultural awareness, deepens their emotional sensitivity, and sharpens their perspective-taking abilities. Beyond mere linguistic proficiency, these language classes are shown to be instrumental in shaping attitudes of tolerance, fostering profound reflection, and nurturing robust intercultural sensitivity. This research critically contributes to the burgeoning field of intercultural pedagogy within language education, offering compelling empirical evidence that underscores the vital importance of implementing experiential, reflective, and culturally integrated curricula within the landscape of Indonesian higher education. The study advocates for a paradigm shift from purely linguistic acquisition to a more holistic approach that prioritizes the development of global citizens capable of empathetic cross-cultural engagement.